1998
DOI: 10.1021/jm980305c
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Quantitative Structure−Activity Relationship Study of the Cannabimimetic (Aminoalkyl)indoles Using Comparative Molecular Field Analysis

Abstract: The present study describes the implementation of comparative molecular field analysis (CoMFA) to develop two 3D-QSAR (quantitative structure-activity relationship) models (CoMFA models 1 and 2) of the cannabimimetic (aminoalkyl)indoles (AAIs) for CB1 cannabinoid receptor binding affinity, based on pKi values measured using radioligand binding assays that displace two different agonist ligands, [3H]CP-55940 and [3H]WIN-55212-2. Both models exhibited a strong correlation between the calculated steric-electrosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 14 publications
5
63
1
Order By: Relevance
“…Our results further suggest that cannabinoid agonist structure may also play a key role in the coupling of CB 1 to G-proteins of both the G q/11 and G i/o classes. Cannabinoid receptor agonists occupy a common binding region within the CB 1 receptor, as demonstrated by their mutual competitive displacement in both radioligand binding assays (Showalter et al, 1996;Felder et al, 1998;Horn et al, 2003) and structure-activity relationship modelling (Shim et al, 1998). However; within the hypothesized binding region, mutagenesis (Song and Bonner, 1996;Chin et al, 1998;McAllister et al, 2003) and molecular modelling (Reggio, 2005;Shim and Howlett, 2006) have demonstrated that the aminoalkylindoles interact with a series of residues distinct from those targeted by classical, non-classical and eicosanoid agonists.…”
Section: Discussionmentioning
confidence: 99%
“…Our results further suggest that cannabinoid agonist structure may also play a key role in the coupling of CB 1 to G-proteins of both the G q/11 and G i/o classes. Cannabinoid receptor agonists occupy a common binding region within the CB 1 receptor, as demonstrated by their mutual competitive displacement in both radioligand binding assays (Showalter et al, 1996;Felder et al, 1998;Horn et al, 2003) and structure-activity relationship modelling (Shim et al, 1998). However; within the hypothesized binding region, mutagenesis (Song and Bonner, 1996;Chin et al, 1998;McAllister et al, 2003) and molecular modelling (Reggio, 2005;Shim and Howlett, 2006) have demonstrated that the aminoalkylindoles interact with a series of residues distinct from those targeted by classical, non-classical and eicosanoid agonists.…”
Section: Discussionmentioning
confidence: 99%
“…At each theoretical level, the changing tendency of the ∆G i values is in fine accordance with the experimental findings even though the changing speed may differ greatly, which may be controlled by the current theoretical levels. MP2 seems to have no substantial advantage over B3LYP, probably a result of intramolecular hydrogen bonding involved in our system instead of intermolecular hydrogen bonding in the system of Costa et al 26 Supposing that DMSO-d 6 would not freeze at 229 K, we calculated the activation free energies at 229, 269, and 316 K. It is shown that, at each specified temperature, the activation free energy is smaller in DMSO-d 6 than in CDCl 3 . The interconversion rate in DMSO-d 6 is about 1.5 times faster than that in CDCl 3 (see Table 1).…”
Section: Theoretical Calculations On the Solvent Effectmentioning
confidence: 97%
“…In CDCl 3 , the coalescence temperatures for H 3 and H 19 are 316 and 304 K. Accordingly, we should have observed the coalescence phenomena in DMSO-d 6 through the variabletemperature NMR experiments from 296 to 375 K. However, no such trace was captured from either 1 H or 13 C NMR spectra (see Figures S1 or S2 of Supporting Information). This may be a result of the faster interconversion rate in DMSO-d 6 than in CDCl 3 . As a result, the coalescence temperature for the same H is lower in DMSO-d 6 than in CDCl 3 .…”
Section: Kinetic Studies Based On Variable-temperature Nmr Experimentsmentioning
confidence: 99%
See 2 more Smart Citations